EFFECTIVENESS OF HUMAN RESOURCES IN IMPROVING THE QUALITY OF LIBRARY SERVICES IN THE DIGITAL ERA - Fitria Agustina, Isna; Firdaus , Vera; Hilda Pandu Winata , Rury (Journal of Geography, Regional Planning and Development, 2024)
Objective: This study aims to analyze the effectiveness of human resources in enhancing the performance of library employees at SMK Negeri 2 Buduran, Sidoarjo Regency. The research focuses on understanding how human resource competence, technological support, and organizational context contribute to the quality of library services in the digital era. Method: A qualitative approach with a case study method was employed. Data were collected through semi-structured interviews with library staff and school management, participant observations of library activities, and analysis of relevant documentation. These methods provided an in-depth understanding of the dynamics influencing employee performance in the library setting. Results: The findings show that the performance of library employees is significantly influenced by three interrelated factors: the competence of human resources, the use of technology (such as automation systems), and contextual elements including leadership support and employee motivation. These factors collectively determine the ability of the library to meet the evolving needs of users. Novelty: This study provides a focused assessment of how human resource effectiveness shapes library performance in a vocational high school environment. It highlights the importance of investing in staff development, optimizing digital tools, and fostering institutional support to create responsive and efficient library services aligned with the demands of the digital age.